2008
DOI: 10.1590/s1519-38292008000300013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados a sintomas de ansiedade em uma coorte de gestantes atendidas em um centro de saúde do município do Rio de Janeiro

Abstract: Objectives: to determine the prevalence and the association between socio-demographic, obstetric and nutritional variables and anxiety symptoms in pregnant women.Methods: the study involved cohorts with five follow-up stages. A cross-sectional analysis was carried out of 151 pregnant women. The presence or absence of anxiety was treated as the dependent variable, which was measured between 19 and 21 weeks of gestation. The State-Trait Anxiety Inventory (STAIT) scale was used to evaluate the anxiety trait. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1
24

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 17 publications
3
15
1
24
Order By: Relevance
“…The anxiety rate observed by this study (16.9%) was relatively low compared to similar studies that observed prevalence rates between 19.8% 27 and 64.9% 28 . These differences may reflect methodological issues related to research design, sample size and characteristics.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The anxiety rate observed by this study (16.9%) was relatively low compared to similar studies that observed prevalence rates between 19.8% 27 and 64.9% 28 . These differences may reflect methodological issues related to research design, sample size and characteristics.…”
Section: Discussioncontrasting
confidence: 83%
“…Women are more vulnerable to mental health problems during pregnancy due to the intense psychological and biological changes that occur during this period 19,21 . The prevalence of symptoms of depression, stress and 12-month prevalence rate of anxiety in women who are not pregnant is 5.9% 22 , 79.3% 23 and 11% 24 , respectively, while prevalence rates of symptoms of depression, anxiety and perceived stress in pregnant women vary between 12.8 and 25% 25,26 , 19.8 27 and 64.9% 28 , and 78% 29,30 and 93% 31 , respectively. Such changes in mental health can result in adverse health outcomes for mother and child, including preterm birth and low birth weight 32 .…”
Section: Introductionmentioning
confidence: 96%
“…No estudo de Anthony e Scialli (1999), em pacientes com o estado de humor alterado, foi observado que a percepção de dor torna-se mais comum. Um dos fatores psicológicos que pode desencadear problema durante a gestação, parto e puerpério, bem como para o concepto, é o aumento do nível de ansiedade; quando reduzido esse nível, os efeitos das dores são minimizados (ARAÚJO et al, 2008). Pimenta (1999) afirma que todas as experiências humanas, inclusive as que causam dores crônicas, envolvem componentes físicos e emocionais (depressão e ansiedade), no entanto, o humor pode ficar comprometido interferindo na interpretação e no relato da dor.…”
Section: Discussionunclassified
“…In previous studies significant associations were identified between the negative body image in pregnant women and certain characteristics, including: high body mass index (BMI) 19 ; inappropriate food attitudes 20,21 ; depressive symptoms 14,22 ; low self-esteem 10,23 ; and high levels of anxiety 24 . Such associations are worrying because they can have negative consequences for health, both for the mother and for the fetus 15 , such as: low birth weight; delayed infantile development; premature birth; and in some cases, abortion 25 . Kamysheva et al 23 , based on the theory of Thompson et al 26 , developed a theoretical model that considered various factors related to the body during pregnancy.…”
Section: Introductionmentioning
confidence: 99%